Short-range order and atomic diffusion in liquid Ge and Si20Ge80 investigated by neutron scattering and x-ray diffraction - Weis, H.; Holland-Moritz, D.; Kargl, F.; Yang, F.; Unruh, T.; Hansen, T. C.; Bednarčik, J.; Meyer, A. (Physical Review B, 2021)
We studied structure and dynamics in liquid Ge and Si20Ge80. Quasielastic neutron scattering (QNS) was employed to accurately determine the Ge self-diffusion coefficient. Static structure factors were measured using neutron and x-ray diffraction. Containerless processing via electromagnetic levitation (EML) enabled to obtain structure factors over a broad temperature range from the metastable regime of the undercooled melt to several hundred Kelvin above the melting point. Moreover, isotopic substitution and combination with x-ray diffraction allowed to determine the partial structure factors SNN(q), SNC(q), SGeGe(q), and SGeSi(q) for liquid Si20Ge80. The topological structures of liquid Ge and Si20Ge80 are very similar. In addition, the Ge self-diffusion coefficients in liquid Ge and Si20Ge80 are equal within error limits.
CRIS-Team Scopus Importer:2021-11-19